Strengthening the character of Nationalism on the Island of Borneo - Suriadi, S; Supriyatno, Triyo; Mursidin, M; Serli, S (Universitas Malikussaleh, 2022)
Borneo is a term that is often used for an alternative name for the island of Kalimantan. This article tries to describe the strengthening of the character of Nationalism in the tail of Borneo. The setting of this research study is in Temajuk Village, Paloh District, Sambas Regency, this is because Temajuk is an area directly adjacent to Malaysia. This study is directed at the aspect of internalizing the value of nationalism through education. The purpose of this study was to determine the potential for opening border areas to social development in the field of education. The results of this study indicate that the sense of nationalism of the citizens of the nation in Temajuk Village is still well maintained, although the attention of the government in the regions and the center of power is still very lacking. This is evidently the various problems that exist in the border areas. Then this is inversely proportional to the